Pendidikan Seks Bagi Anak Sejak Dini Persfektif Gender sebagai Bentuk Kemandirian dalam Lingkungan Sosial - Gusti Ayu Agung Riesa Mahendradhani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Sex education is a taboo to discuss, especially if it is concerned with the words children or adolescents. They tend to be protected from the word sex and are isolated from the adult world because they are their children who do not deserve to know about the essence of sex itself according to adults. Surrounding people limit children's knowledge about what is the essence of sex itself. A good social environment will affect children's growth and development such as self-confidence, ability to do things, high motivation, unyielding attitude, responsibility and trust in others. To form a good social environment, parents must have a high level of trust in children when children grow up. As parents, worry is undeniable, but minimizing worry by providing various education to children is a better solution than limiting the child's social environment. One of the important education provided is sex education for children from an early age. Sex education is expected to fortify children from promiscuity that tends to be negative and to choose a productive social environment to develop children's abilities and personalities to become more independent.